2019
DOI: 10.5935/0103-507x.20190010
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-lymphocyte ratio in the early diagnosis of sepsis in an intensive care unit: a case-control study

Abstract: Objective To evaluate the neutrophil-lymphocyte ratio as a predictor of sepsis and mortality in patients admitted to an intensive care unit. Methods Case-control study of adult patients admitted to an intensive care unit. Patients who had sepsis as the reason for admission and who had a previous complete blood count examination were included as case patients. The following statistical analyses were performed: ROC curves, binary logistic regression, and Mann-Whitney and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 39 publications
1
60
1
6
Order By: Relevance
“…This study is consistent with previous studies considering NLR as a prognostic marker of sepsis [10][11][12]. These studies proposed NLR not only as a predictor of sepsis but also as a marker of disease severity and worse outcome.…”
Section: Discussionsupporting
confidence: 93%
“…This study is consistent with previous studies considering NLR as a prognostic marker of sepsis [10][11][12]. These studies proposed NLR not only as a predictor of sepsis but also as a marker of disease severity and worse outcome.…”
Section: Discussionsupporting
confidence: 93%
“…Many hematological parameters are currently been utilized to predict outcomes and mortality in patients infected with SARS CoV-2. The neutrophil to lymphocyte ratio (NLR), is an inflammatory mediator used as predictor of systemic inflammation [ 1 ]. Numerous studies conducted around globe have reported about neutrophil to lymphocyte ratio (NLR) as a predictor of prognosis in a variety of cancers (breast, ovary, lung), cardiovascular disorders (coronary procedures and coronary artery bypass grafting), infectious disorders (community-acquired pneumonia, corona) and sepsis in general [ 1–5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The neutrophil to lymphocyte ratio has been used as an inflammatory index [45] and can be calculated from cell counts obtained from a routine full or complete blood count. Its use in the setting of sepsis has been suggested as being potentially most useful in low-or middle-income countries, as it does not require any extra specific analytical capability or cost outlay [46], although its diagnostic accuracy does seem to be limited [46][47][48] and well below that of CRP [48].…”
Section: Number Of Studiesmentioning
confidence: 99%